Development of a PC Program for Multivariate Statistical Analysis - Son, Pham Ngoc; Vu, Cao Dong; Anh, Mai Quynh (Communications in Physics, 2017)
This report introduces a new computer program, having been developed initially at the Nuclear Research Institute at Dalat, for the multivariate data analysis techniques. In this preliminary version of the program, the size of a given data set to be analyzed is up to 50 variables and thousand observations, and can be used to perform some of the multivariate data analysis techniques such as principle component analysis, cluster analysis and data standardization. In comparison with other statistical analysis software, the same results are highly reproduced with MSAP.